Clinical Predictors of Sensorineural Hearing Loss and Cognitive Outcome in Infants with Symptomatic Congenital Cytomegalovirus Infection. Issue 8 (August 2016) - Pinninti, Swetha G.; Rodgers, Mackenzie D.; Novak, Zdenek; Britt, William J.; Fowler, Karen B.; Boppana, Suresh B.; Ross, Shannon A.
Abstract : The objective of this study was to determine newborn clinical findings predictive of adverse clinical outcomes in infants with symptomatic congenital cytomegalovirus infection. Of 160 infants, significantly more children with central nervous system involvement had sensorineural hearing loss ( P = 0.0007) and an IQ ⩽70 ( P < 0.0001) compared with infants with transient findings or only a petechial rash. Abstract : Supplemental Digital Content is available in the text.